The Structure of the RNA-Dependent RNA Polymerase of a Permutotetravirus Suggests a Link between Primer-Dependent and Primer-Independent Polymerases. - Diego S Ferrero; Mònica Buxaderas; José F Rodríguez; Núria Verdaguer (PLoS Pathogens, 2015)
Thosea asigna virus (TaV), an insect virus belonging to the Permutatetraviridae family, has a positive-sense single-stranded RNA (ssRNA) genome with two overlapping open reading frames, encoding for the replicase and capsid proteins. The particular TaV replicase includes a structurally unique RNA-dependent RNA polymerase (RdRP) with a sequence permutation in the palm sub-domain, where the active site is anchored. This non-canonical arrangement of the RdRP palm is also found in double-stranded RNA viruses of the Birnaviridae family. Both virus families also share a conserved VPg sequence motif at the polymerase N-terminus which in birnaviruses appears to be used to covalently link a fraction of the replicase molecules to the 5'-end of the genomic segments. Birnavirus VPgs are presumed to be used as primers for replication initiation. Here we have solved the crystal structure of the TaV RdRP, the first non-canonical RdRP of a ssRNA virus, in its apo- form and bound to different substrates. The enzyme arranges as a stable dimer maintained by mutual interactions between the active site cleft of one molecule and the flexible N-terminal tail of the symmetrically related RdRP. The latter, partially mimicking the RNA template backbone, is involved in regulating the polymerization activity. As expected from previous sequence-based bioinformatics predictions, the overall architecture of the TaV enzyme shows important resemblances with birnavirus polymerases. In addition, structural comparisons and biochemical analyses reveal unexpected similarities between the TaV RdRP and those of Flaviviruses. In particular, a long loop protruding from the thumb domain towards the central enzyme cavity appears to act as a platform for de novo initiation of RNA replication. Our findings strongly suggest an unexpected evolutionary relationship between the RdRPs encoded by these distant ssRNA virus groups.